Mi monstruo Mandarino - Murguía, Verónica 1960- (Artes de México [u.a.], 2007)
El unico amigo de Andrea era un monstruo que se llamaba Mandarino Plátanos. Aunque él la acompañaba a todas partes, nadie era capaz de verlo. Un día, Andrea descubrió que también podía jugar con otras niñas y, al percatarse de ello, Mandarino tomó una decisión. - Andrea's only friend is a monster named Mandarino Plátanos. Although he accompanies her everywhere, nobody is able to see him. One day, Andrea discovers that she can also play with other children and when Mandarino notices this, he makes a decision
Keywords: Monsters / Juvenile fiction; Imaginary companions / Juvenile fiction; Friendship / Juvenile fiction; Monsters / Fiction; Imaginary playmates / Fiction; Friendship / Fiction; Spanish language materials; Monstruos / Novela juvenil; Compañeros imaginarios / Novela juvenil; Amistad / Novela juvenil; Bindungslosigkeit; Fantasiegefährte; Freundschaft; Abschied; Bilderbuch